Investigación periodística sobre el microtráfico y la criminalidad en el sector de La Mariscal - Ortega Reyes, Juan Javier (2015)
Journalistically to address issues related to crime and the drug trade was inescapable review before concepts related to communication, research and security. The first must be understood as one key feature in the development of society. By nature, man is a social animal who needs the other to survive, to interact. Research is inherent in the communication. Since prehistoric times, humans have sought resources and mechanisms to survive. That is, a natural and pragmatic research. Since time immemorial man has investigated their environment and created a number of tools such as innate method for the survival of the species. These notions -communication, research- stand as the foundation for deepening the phenomenon of micro-trafficking and crime. This paper focuses on elucidating what is behind the drug trade and the crimes perpetrated in La Mariscal between 2010 and 2012. And within this dual notion, the issue of security is directly linked. The discussion of public safety is relatively new. Scholars who have taken the time to analyze violence in the region argue that the term began using it in the late eighties, when Latin American countries put aside to make way dictatorships to democracies. This work, besides presenting a detailed analysis of these categories -communication, research, security- reveals clandestine operations that run in La Mariscal neighborhood has the highest concentration of bars and nightclubs in Quito. Thus, this publication aims to provide readers a theoretical and practical tool for investigative journalism and a basis for future research on the relationship of the sale of narcotics in neighborhoods and territory disputes between criminal mafias.